2020
DOI: 10.1111/ahe.12646
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical study of the dorsal and ventral nasal conchal bullae and middle nasal conchae in normal Shetland ponies: Computed tomographic anatomical and morphometric findings

Abstract: Equine paranasal sinuses are susceptible to inflammation. Insufficient drainage through the nasal passages and meatus may lead to the accumulation of inspissated purulent discharge. Particularly in ponies, these anatomical structures are suspected to be relatively small. To date, there are no reports considering the morphology of nasal conchal bullae in small horse breeds such as Shetland ponies. The aim of the present study was to How to cite this article: Gerlach K, Vervuert I, Gittel C, et al.An anatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…In our study, we found that Noma horses had a relatively longer nasal length than cranial length, which is clearly indicated by the cranial length/nasal length quotient of 0.90, compared with 0.96 in large breeds (Evans & McGreevy, 2006), 1.06 in Shetland ponies (Gerlach et al, 2021), and 1.08 in donkeys (Zhu et al, 2014) (Table 5). Furthermore, the skull index of Noma horses was the shortest in comparison with that of the other breeds, apart from large breeds.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…In our study, we found that Noma horses had a relatively longer nasal length than cranial length, which is clearly indicated by the cranial length/nasal length quotient of 0.90, compared with 0.96 in large breeds (Evans & McGreevy, 2006), 1.06 in Shetland ponies (Gerlach et al, 2021), and 1.08 in donkeys (Zhu et al, 2014) (Table 5). Furthermore, the skull index of Noma horses was the shortest in comparison with that of the other breeds, apart from large breeds.…”
Section: Discussionsupporting
confidence: 52%
“…Correlations between the length measurements were calculated using Spearman's rank correlation coefficient, which can be interpreted as follows: 0.8 ≤ | r | ≤ 1.0, very strong; 0.6 ≤ | r | < 0.8, strong; 0.4 ≤ | r | < 0.6, moderate; 0.2 ≤ | r | < 0.4, weak; and 0.0 ≤ | r | < 0.2, very weak (| r | represents the absolute value of the correlation coefficient). On considering the different conformations of the skull by evaluating the relationships between bulla dimensions, ‘adjusted’ measurements of the DCB and VCB dimensions were calculated by dividing the individual bulla length by skull length 2 and multiplying the result into 100 (Froydenlund et al, 2015; Gerlach et al, 2021). Correlations between the volumes, head length and head width were calculated using Spearman's rank correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations